Hospital admission for neurologic disorders among 5‐year survivors of noncentral nervous system tumors in childhood: A cohort study within the Adult Life after Childhood Cancer in Scandinavia study. Issue 3 (29th April 2019) - Kenborg, Line; Linnet, Karen M.; de Fine Licht, Sofie; Bautz, Andrea; Holmqvist, Anna S.; Tryggvadottir, Laufey; Madanat‐Harjuoja, Laura M.; Stovall, Marilyn; Heilmann, Carsten; Albieri, Vanna; Hasle, Henrik; Winther, Jeanette F.; et al.
Abstract : Large, comprehensive studies of the risk for neurologic disorders among long‐term survivors of noncentral nervous system (CNS) childhood cancers are lacking. Thus, the aim of our study was to assess the lifetime risk of Nordic non‐CNS childhood cancer survivors for neurologic disorders. We identified 15, 967 5‐year survivors of non‐CNS childhood cancer diagnosed in Denmark, Iceland, Finland and Sweden in 1943–2008, and 151, 118 matched population comparison subjects. In‐patient discharge diagnoses of neurologic disorders were used to calculate relative risks (RRs) and absolute excess risks (AERs). A neurologic disorder was diagnosed in 755 of the survivors while 370 were expected, yielding a RR of 2.0 (95% confidence interval (CI) 1.9–2.2). The highest risks were found among survivors of neuroblastoma (4.1; 95% CI 3.2–5.3) and leukemia (2.8; 95% CI 2.4–3.2). The AER decreased from 331 (278–383) excess neurologic disorders per 100, 000 person‐years 5–9 years after diagnosis to 82 (46–118) ≥ 20 years after diagnosis. Epilepsy was the most common diagnosis ( n  = 229, 1.4% of all survivors), and significantly increased risks were seen among survivors of eight out of 12 types of childhood cancer. Survivors of neuroblastoma had remarkably high risks (RR ≥ 10) for hospitalization for paralytic syndromes and hydrocephalus, while survivors of leukemia had additional high risks for dementia and encephalopathy. In conclusion, survivors of non‐CNS childhood cancer are at high risk for neurologic disorders, especially within the first decade after diagnosis. Therefore, intensive follow‐up to identify those who require close management is needed. Abstract : What's new? Although several studies have demonstrated increased risks for a wide range of late complications among survivors of non‐central nervous system (CNS) cancers in childhood, a comprehensive overview of neurologic disorders in this population is lacking. In a population‐based cohort study of 15, 967 five‐year survivors, the authors report increased risks for several neurologic disorders, including epilepsy, paralytic syndromes, meningitis, hydrocephalus and nerve and degenerative disorders, with highest risks among survivors of neuroblastoma and leukemia. This is the first step toward identifying those survivors who will benefit from closer follow‐up to prevent severe neurologic disorders leading to hospitalization.